From Puritan to Yankee : character and the social order in Connecticut, 1690-1765 - Bushman, Richard L. (A publication of the Center for the Study of the History of Liberty in America, Harvard University, 1967)
The years from 1690 to 1765 in America have usually been considered a waiting period before the Revolution. Mr. Bushman, in his penetrating study of colonial Connecticut, takes another view. He shows how, during these years, economic ambition and religious ferment profoundly altered the structure of Puritan society, enlarging the bounds of liberty and inspiring resistance to established authority. This is an investigation of the strains that accompanied the growth of liberty in an authoritarian society. Mr. Bushman traces the deterioration of Puritan social institutions and the consequences for human character. He does this by focusing on day-to-day life in Connecticut--on the farms, in the churches, and in the town meetings. Controversies within the towns over property, money, and church discipline shook the "land of steady habits," and the mounting frustration of common needs compelled those in authority, in contradiction to Puritan assumptions, to become more responsive to popular demands. In the Puritan setting these tensions were inevitably given a moral significance. Integrating social and economic interpretations, Mr. Bushman explains the Great Awakening of the 1740's as an outgrowth of the stresses placed on the Puritan character. Men, plagued with guilt for pursuing their economic ambitions and resisting their rulers, became highly susceptible to revival preaching. The Awakening gave men a new vision of the good society. The party of the converted, the "New Lights," which also absorbed people with economic discontents, put unprecedented demands on civil and ecclesiastical authorities. The resulting dissension moved Connecticut, almost unawares, toward republican attitudes and practices. Disturbed by the turmoil, many observers were, by 1765, groping toward a new theory of social order that would reconcile traditional values with their eighteenth-century experiences. Vividly written, full of illustrative detail, the manuscript of this book has been called by Oscar Handlin one of the most important works of American history in recent years. Table of Contents: PART ONE: SOCIETY IN 1690 1. Law and Authority 2. The Town and the Economy PART TWO: LAND, 1690-1740 3. Proprietors 4. Outlivers 5. New Plantations 6. The Politics of Land PART THREE: MONEY, 1710-1750 7. New Traders 8. East versus West 9. Covetousness PART FOUR: CHURCHES, 1690-1765 10. Clerical Authority 11. Dissent 12. Awakening 13. The Church and Experimental Religion 14. Church and State PART FIVE: POLITICS, 1740-1765 15. New Lights in Politics 16. A New Social Order Appendixes Bibliographical Note List of Works Cited Index Illustrations Map of Connecticut in 1765 Map of hereditary Mohegan lands and Wabbaquasset lands Reviews of this book: Employing his special training in psychology to advantage, Bushman has skillfully woven into his description and analysis of Connecticut society in the process of change, a bold interpretation of the impact of change upon individual character formation. The author has made a signal contribution to the history of liberty in America.--William and Mary QuarterlyReviews of this book: At the heart of history lies a vague but undeniable substance known as 'national character' or 'social character'. Richard L. Bushman has had the courage to offer his version of the evolution of the social character of Connecticut. The boldness of the attempt alone would make Puritan to Yankee an important book, but it is the general accuracy of its author's perception of the way the mechanism of historical change operates and the specific accuracy 0f his assessment of the results that makes the book one of the most fruitful historical studies produced in the last few years in any field of history.--History and TheoryReviews of this book: Professor Bushman's study of eighteenth-century Connecticut is a first-rate job of social history. He deals with large questions in satisfying detail. Energy in research is combined with courage in writing.--New England Quarterly